Analysis Of Android-Based Online Message Gateway Towards The Use Of Plastic Bags On PKK Mother - Ali Sodik, Muhammad; Maulina, Dhea (Journal of Global Research in Public Health, 2021)
The use of plastic bags is increasing with the development of technology, industry and population. Community dependence on plastic products is indeed very large. Ranging from household products, stationery, medical devices, building materials, etc. many are made from plastic. It is undeniable that there are many plastic-based equipment that are sold at relatively cheap prices, making it affordable for the community. As a result, plastic waste is also generated. Therefore, socialization or education to reduce the use of plastic bags should be intensified. For maximum education, an appropriate method needs to be used. So the researchers used an approach with the Android-Based Online Message Gateway to the PKK Mother. The research design used was pre experimental design. With a population of 64 PKK mothers in the Kelurahan Manisrenggo, they use a simple random sampling technique so that a sample of 56 respondents. Using the Wilcoxon statistical test with a significance level of 0.05. The results showed that the significance value of the attitude variable 0,000 <0.05 and the significant value of the action variable 0,000 <0.05. So, if Ho and H1 are rejected, then there is the influence of Android-Based Online Message Gateway on Attitudes and Action in the Use of Plastic Bags in PKK Mothes in Kelurahan Manisrenggo, Kota Kediri.